Upregulation of TLR4/MyD88 pathway in alcohol-induced Wernicke’s encephalopathy: Findings in preclinical models and in a postmortem human case - Moya, Marta; Escudero, Berta; Gómez-Blázquez, Elena; Rebolledo-Poves, Ana Belen; López-Gallardo, Meritxell; Guerrero, Carmen; Marco, Eva M.; Orio, Laura (Frontiers in Pharmacology, 2022)
Wernicke’s encephalopathy (WE) is a neurologic disease caused by vitamin B1 or thiamine deficiency (TD), being the alcohol use disorder its main risk factor. WE patients present limiting motor, cognitive, and emotional alterations related to a selective cerebral vulnerability. Neuroinflammation has been proposed to be one of the phenomena that contribute to brain damage. Our previous studies provide evidence for the involvement of the innate immune receptor Toll-like (TLR)4 in the inflammatory response induced in the frontal cortex and cerebellum in TD animal models (animals fed with TD diet [TDD] and receiving pyrithiamine). Nevertheless, the effects of the combination of chronic alcohol consumption and TD on TLR4 and their specific contribution to the pathogenesis of WE are currently unknown. In addition, no studies on TLR4 have been conducted on WE patients since brains from these patients are difficult to achieve. Here, we used rat models of chronic alcohol (CA; 9 months of forced consumption of 20% (w/v) alcohol), TD hit (TDD + daily 0.25 mg/kg i.p. pyrithiamine during 12 days), or combined treatment (CA + TDD) to check the activation of the proinflammatory TLR4/MyD88 pathway and related markers in the frontal cortex and the cerebellum. In addition, we characterized for the first time the TLR4 and its coreceptor MyD88 signature, along with other markers of this proinflammatory signaling such as phospo-NFκB p65 and IκBα, in the postmortem human frontal cortex and cerebellum (gray and white matter) of an alcohol-induced WE patient, comparing it with negative (no disease) and positive (aged brain with Alzheimer’s disease) control subjects for neuroinflammation. We found an increase in the cortical TLR4 and its adaptor molecule MyD88, together with an upregulation of the proinflammatory signaling molecules p-NF-ĸB and IĸBα in the CA + TDD animal model. In the patient diagnosed with alcohol-induced WE, we observed cortical and cerebellar upregulation of the TLR4/MyD88 pathway. Hence, our findings provide evidence, both in the animal model and the human postmortem brain, of the upregulation of the TLR4/MyD88 proinflammatory pathway in alcohol consumption–related WE.